Effect of the SiO2/Al2O3 ratio on the synthesis of Na-x zeolite from Mae Moh fly ash - Thuadaij P. (Science Society of Thailand under Royal Patronage, 2015)
In this study, a Na-x zeolite was synthesized by using metakaolin from Narathiwat kaolinite, amorphous silica from rice husk ash, and high CaO fly ash from the Mae Moh electrical plant by using the alkaline fusion method. The mixture of fly ash, amorphous silica and metakaolin was fused in NaOH followed by incubation at 70 °C for 24 h. An amorphous silica from rice husk ash and metakaolin were added to high CaO fly ash to increase the SiO 2/Al2O3 ratio of fusion materials. The fused mixtures of high CaO fly ash, amorphous silica and metakaolin were mixed in the weight ratio of 1:3:6 giving a SiO2/Al2O3 ratio of 3.25 to achieve a Na-x zeolite phase. The synthesized zeolite was characterized by XRD, SEM, FTIR, and BET techniques. The CEC and specific surface area of the Na-x zeolite were 420 meq 100 g-1 and 398 m 2/g, respectively. Copyright © 2005 ScienceAsia.